2005
DOI: 10.1002/biof.5520250129
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 supplementation reduces corticosteroids dosage in patients with bronchial asthma

Abstract: Data show that patients with corticosteroid-dependent bronchial asthma have low plasma CoQ(10) concentrations that may contribute to their antioxidant imbalance and oxidative stress. A reduction in the dosage of corticosteroids required by the patients following antioxidant supplementation was observed, indicating lower incidence of potential adverse effects of the drugs, decreased oxidative stress. This study also demonstrates the significant uptake of CoQ(10) by lung tissue in a rat model using hydrosoluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
(14 reference statements)
0
24
0
1
Order By: Relevance
“…This is probably because the surge of mtROS is too high to be countered by antioxidants or that the oxidative damage sustained by mitochondria is too far gone to be helped by belated quenching of ROS. However, the mitochondrial antioxidant coenzyme Q10 and its derivative Mito Q are being looked upon as potential therapeutic molecules, after a study involving steroid-dependent asthma patients administered with a daily dose of coenzyme Q10, alpha tocopherol and vitamin C showed increased corticosteroid sensitivity [74]. It is important to note that untargeted quenching of ROS could achieve different results in different cells.…”
Section: Mitochondrial Targeted Therapy In Allergy Asthma and Metabomentioning
confidence: 98%
“…This is probably because the surge of mtROS is too high to be countered by antioxidants or that the oxidative damage sustained by mitochondria is too far gone to be helped by belated quenching of ROS. However, the mitochondrial antioxidant coenzyme Q10 and its derivative Mito Q are being looked upon as potential therapeutic molecules, after a study involving steroid-dependent asthma patients administered with a daily dose of coenzyme Q10, alpha tocopherol and vitamin C showed increased corticosteroid sensitivity [74]. It is important to note that untargeted quenching of ROS could achieve different results in different cells.…”
Section: Mitochondrial Targeted Therapy In Allergy Asthma and Metabomentioning
confidence: 98%
“…Because of its hydrophobicity and large molecular weight, the absorption of dietary CoQ 10 is slow and limited. Gvozdjáková et al (1999Gvozdjáková et al ( , 2002Gvozdjáková et al ( , 2004Gvozdjáková et al ( , 2005 following their research reported high bioavailability of CoQ 10 in capsules in its hydrosoluble form. According to US Patent (2003) good absorption of CoQ 10 is in capsules in its oil-water emulsion form.…”
Section: Nutritional Supplementmentioning
confidence: 99%
“…Gazdík et al (2002) described significantly decreased levels of CoQ 10 and α-tocopherol both in plasma and blood in patients with bronchial asthma, as compared with healthy subjects. Gvozdjáková et al (2005) did a study which showed that patients with corticosteroid-dependent bronchial asthma had low plasma CoQ 10 concentrations which might contribute to their antioxidant imbalance and oxidative stress. The reduction in the dosage of corticosteroids required by the patients following the antioxidant supplementation means a lower incidence of adverse effects due to the drugs.…”
Section: Coq 10 and Diseasesmentioning
confidence: 99%
“…Coenzyme Q and vitamin E are mitochondria-targeted antioxidants. Notably, coenzyme Q10 is known to reduce the requirement of corticosteroids in asthmatic patients [ 21 ]. Further, using experimental mouse models, we have shown that L-arginine and statins alleviate asthma features and improve mitochondrial function in lungs, possibly due to restoration of homeostatic nitric oxide metabolism in bronchial epithelia [ 69 , 122 ].…”
Section: Therapeuticsmentioning
confidence: 99%
“…It had previously been shown that a mitochondria-targeted antioxidant, coenzyme Q10, reduced corticosteroid requirement in asthmatic patients [ 21 ]. The benefi ts of targeting mitochondria with antioxidants such as vitamin E and N-acetyl-L-cysteine (NAC) in allergic diseases [ 22 , 23 ] supported the possible involvement of mitochondria in allergic diathesis.…”
Section: Introductionmentioning
confidence: 98%